Kognitywne aspekty glottodydaktyki. Czeski student wobec pułapek komunikatywności - Hofmański, Wojciech (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
Foreign language learners are commonly taught explicit rules of grammar, but often fail to apply them when confronted with communicative tasks. The article provides analyses on linguistic errors encountered by teachers during language teaching processes effected in homogeneous, all-Czech groups participating in language courses. Additionally, the article discusses the problem of comprehending the glottodidactical (language education) process within the context of a particular communicative situation (cognitive approach). The main focus of the study relates to competitive planes that are subject to the occurence of linguistic interference. A particular attention is given to pronunciation, grammar (inflection and syntax), and to lexis. For primarily Czech-speaking users of the Polish language, the biggest difficulty as far as the pronunciation is concerned, is the pronunciation of alveolo-palatal consonants and palatal hard consonants that are not appropriately differntiated in their realisation (this refers in particular to [ś] and [š], but also to [č] and [ć] ). A similar problem occurs in vowels – a hard vowel [y] is frquently replaced by a soft vowel [i]. A considerable number of occurences of the dental-alveolar [l] in place of the expected [] is identified and discussed. Within the domain of inflection, the article addresses the problem of the apparent equivalence at the level of the plural nominative and singular genetive of masculine nouns (the occurence of regular interference has been demonstrated), whereas a syntactical analysis has made it possible to indicate modifications at the linear level of utterances that are mainly related to an erroneous location of the Polish reflexive pronoun “się”. With regard to lexis, the division of difficulties to be found within the glottodidactical process is raised (semantic, stylistical and onimic difficulties). Additionally, the article discusses the danger of the abuse of colloquial vocabulary in communiques created in informal situations. Key words: teaching of Polish as